Tunable photonic band-gaps in one-dimensional photonic crystals containing linear graded index material - Singh B.K.; Kumar P.; Pandey P.C. (My University, 2025)
We have demonstrated control of the photonic band gaps (PBGs) in 1-D photonic crystals using linear graded index material. The analysis of PBG has been done in THz region by considering photonic crystals in the form of ten periods of second, third and fourth generation of the Fibonacci sequence as unit cell. The unit cells are constituted of two kinds of layers; one is taken of linear graded index material and other of normal dielectric material. For this investigation, we used a theoretical model based on transfer matrix method. We have obtained a large number of PBGs and their bandwidths can be tuned by changing the grading profile and thicknesses of linear graded index layers. The number of PBGs increases with increase in the thicknesses of layers and their bandwidths can be controlled by the contrast of initial and final refractive index of the graded layers. In this way, we provide more design freedom for photonic devices such as reflectors, filters, optical sensors, couplers, etc. © 2014, Springer-Verlag Berlin Heidelberg.